The influence of tourist experience on destination loyalty to Islamic architectural sites in Putrajaya. - Mohd Kamaruzaman, Nur Amalin; Saad, Mazni (2020)
Islamic tourism is a new trend of tourism product which seen as a new contributor to Malaysia’s economy, especially in the tourism and hospitality industry. Although Islamic tourism currently has risen to the level of popularity in Malaysia, limited academic research is available in experiential perspectives of Islamic tourism towards destination loyalty, especially in Islamic architectural settings; resulting in a gap in such knowledge. In particular, the lack of research shows that there is limited understanding on the effect of tourist experience on destination loyalty. Therefore, this study desires to examine the influence of tourist experience, namely visual experience, emotional experience and engaging experience on destination loyalty to Islamic architectural sites in Putrajaya, Malaysia. This city is selected as a site of investigation for this study because it is claimed to be of a ‘true and progressive’ Malaysian-Islamic architectural expression. The data from this study were collected from 155 domestic tourists visiting Islamic architectural sites in Putrajaya through a convenience sampling method, using a structured questionnaire. This study employed descriptive statistics (frequency, percentage, mean and S.D) and inferential statistics (multiple regression analysis) to analyze the data. The results showed statistically significant influence of tourist experience; visual experience, emotional experience and engaging experience on destination loyalty. Overall, this study has confirmed the assumption that there is a significant influence of tourist experience on destination loyalty where visual experience is the most influential tourist experience in revisiting Islamic architectural sites in Putrajaya.